Prospective analysis of the antiepileptic potential of species from the Passifloraceae, Zingiberaceae and Cannabaceae families (Research, Society and Development, 2024)
Epilepsy is a chronic neurological condition characterized by recurrent seizures and without a definitive cure, significantly impacting patients' quality of life. Conventional treatment involves the use of antiepileptic drugs, which, although effective in controlling seizures, can cause a series of harmful side effects and do not address the underlying cause of the disease. Additionally, patients with drug-resistant epilepsy face additional challenges, including cognitive impairment and low educational and occupational performance. In this context, researching new treatment alternatives for epilepsy becomes crucial. A promising area is the study of natural extracts from medicinal plants, which have been investigated for their antiepileptic potential. This study focuses on the Passifloraceae, Zingiberaceae, and Cannabaceae families due to their richness in bioactive compounds with pharmacological properties. Scientific research has revealed that several species from these plant families possess antiepileptic and anticonvulsant activities, providing a basis for the development of new treatments. However, the challenges faced in obtaining patents and developing herbal products in Brazil highlight the need for additional investments and clear regulatory policies in this area. Therefore, continuous research on the therapeutic potential of medicinal plants, along with efforts to improve access to innovative treatments, is essential to enhance epilepsy management and patients' quality of life.